2011
DOI: 10.2174/092986711798347333
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of Host Immunity by Virulent Salmonella: Implications for Vaccine Design

Abstract: Dendritic cells (DCs) are professional antigen presenting cells (APCs) capable of linking innate and adaptive immunity during infection. After recognition of pathogen-associated molecular patterns (PAMPs), DCs can engulf, process and present bacteria-derived antigens on MHC molecules to T cells. Because of the key role that DCs play on the initiation of innate and adaptive immunity, alterations in their function could render the host susceptible to bacterial dissemination. Consistent with this notion, is the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In support of this observation are recent studies describing how only partial extracellular engagement of FcγRIII or FcγRI in the surface of an antigen‐presenting cell is enough to trigger a strong intracellular degradative pathway, which renders host cells able to fuse early/late endosomes with lysosomal compartments 66 . Hence, this observation unifies our findings and suggests that superficial IgGs, being present in ICs, could be engaging FcγRIII in the surface of the DCs and triggering a strong degradative pathway that promotes the fusion of already internalized Salmonella ‐ICs (engulfed without the assistance of FcγRs) with lysosomes 24,45 . Interestingly, the degradation of ST‐IgG within DCs was characterized as a function of PI3K 24 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In support of this observation are recent studies describing how only partial extracellular engagement of FcγRIII or FcγRI in the surface of an antigen‐presenting cell is enough to trigger a strong intracellular degradative pathway, which renders host cells able to fuse early/late endosomes with lysosomal compartments 66 . Hence, this observation unifies our findings and suggests that superficial IgGs, being present in ICs, could be engaging FcγRIII in the surface of the DCs and triggering a strong degradative pathway that promotes the fusion of already internalized Salmonella ‐ICs (engulfed without the assistance of FcγRs) with lysosomes 24,45 . Interestingly, the degradation of ST‐IgG within DCs was characterized as a function of PI3K 24 .…”
Section: Discussionsupporting
confidence: 88%
“…This leads to reduced availability of the intracellular bacterial‐derived antigens necessary to produce T‐cell‐activating antigen‐loaded MHCs 43,44 . IgG‐opsonization of the pathogen before infection restores the capacity of DCs to prime antigen‐specific naive T cells 23,24,45 . However, little is known about how IgG‐opsonization could enhance bacterial degradation/antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we provide evidence that the interference in the fusion between late endosomes and lysosomes can be the cause for reduced presentation on class MHC‐II molecules. In agreement with these data, it has been previously shown that the accumulation of pathogens in Rab7 + vesicles decreases late phagosome‐to‐lysosome fusion, thus reducing the efficiency of antigen presentation and that decreased destination of pathogens to Lamp1 + compartments drastically decrease antigen presentation in both class I and class II MHCs because lysosomes have the full repertoire for MHCs and peptide mounting during endo/lysosomal trafficking mainly occurs in these late acidic vesicles .…”
Section: Discussionsupporting
confidence: 77%
“…Salmonella has evolved many mechanisms to contend with adverse environments imposed by the host and to suppress or modulate induction of immune responses mainly by SPI-2 effectors [176]. Although many mechanisms still need to be elucidated, much progress has been made to facilitate attenuated vaccine development.…”
Section: Other Important Rasv Attributesmentioning
confidence: 99%